2003
DOI: 10.1002/bin.129
|View full text |Cite
|
Sign up to set email alerts
|

Promoting social initiation in children with autism using video modeling

Abstract: A large number of studies have shown that children and youths with autism can improve their social skills when provided with appropriate and well planned treatment strategies. Here, a video modeling procedure was implemented with seven developmentally delayed children, using a multiple-treatment design. Each child watched a videotape showing a model and the experimenter engaged in a simple social interactive play in an adapted play setting. Afterwards each child’s behavior was assessed in this setting, while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
134
0
11

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 169 publications
(151 citation statements)
references
References 26 publications
6
134
0
11
Order By: Relevance
“…Verbal instructions, modeling in vivo, and behavior rehearsal were the techniques used to teach the model how to perform the required behaviors in the videotapes; only this child and the experimenter were shown in each videotape. A peer was selected as a model because findings of previous experiments showed that children with autism could learn equally well from both adults and peers as models (Ihrig & Wolchik, 1988), either familiar or unfamiliar ones (Nikopoulos & Keenan, 2003). In all videotapes, the model was shown emitting a social initiation to the experimenter, before they both together engaged in an activity or a sequence of activities.…”
Section: Settingsmentioning
confidence: 99%
“…Verbal instructions, modeling in vivo, and behavior rehearsal were the techniques used to teach the model how to perform the required behaviors in the videotapes; only this child and the experimenter were shown in each videotape. A peer was selected as a model because findings of previous experiments showed that children with autism could learn equally well from both adults and peers as models (Ihrig & Wolchik, 1988), either familiar or unfamiliar ones (Nikopoulos & Keenan, 2003). In all videotapes, the model was shown emitting a social initiation to the experimenter, before they both together engaged in an activity or a sequence of activities.…”
Section: Settingsmentioning
confidence: 99%
“…All the participants viewed the same videotape. The selection of a typically developing peer as a model was based on the finding of our previous study (Nikopoulos & Keenan, 2003) wherein all three different models (i.e., a familiar adult, an unfamiliar adult, & a typically developing peer) were equally effective. Also, previous research has suggested that children with autism could learn equally well from both adults and peers as models (Ihrig & Wolckik, 1988).…”
Section: Stimulus Materialsmentioning
confidence: 99%
“…In addition, video modelling could serve as an efficient cost-effective tool, negating the high cost of live models employed in many kinds of training programmes (Racicot & Wogalter, 1995). Although, literature has demonstrated that video modelling can be effective in teaching a variety of different behaviours such as teaching generalisation of purchasing skills across community settings (Haring et al, 1987(Haring et al, , 1995, functional living skills (Shipley-Benamou, Lutzker, & Taubman, 2002), perspective taking (CharlopChristy & Daneshvar, 2003), verbal and motor responses (D'Ateno, Mangiapanello, & Taylor, 2003), and generative spelling (Kinney, Vedora, & Stromer, 2003), promoting social initiation (Nikopoulos & Keenan, 2003), enhancing conversational skills (Charlop & Milstein, 1989;Sherer et al, 2001), increasing play-related comments of children with autism towards their siblings (Taylor et al, 1999), reducing disruptive transition behaviour (Schreibman, Whalen, & Stahmer, 2000) currently there are no published studies examining the generalised effects of video modelling in the enhancement of social initiation and reciprocal play by children with autism.…”
mentioning
confidence: 99%
“…However, for some children, VBIs have little or no effect, wasting valuable time, energy and resources with limited benefit for the child [6,7,8]. There are still many unanswered questions regarding what prerequisite skills are necessary to enable children with ASD to benefit from VBIs.…”
mentioning
confidence: 99%
“…In another study, Nikopoulos and Keenan [8] used VBI to teach social initiation skills to seven children with autism aged between nine and 15. The participants watched a video of an adult requesting a child to engage in play.…”
mentioning
confidence: 99%